Role of Bottom-up and Top-down Pre-listening Activities on Iranian EFL Students’ Listening Comprehension - Fatemeh Karimi; Azizeh Chalak (Journal of Modern Research in English Language Studies, 2021)
AbstractPre-listening activity has a considerable role in improving listening comprehension. This research examined the effects of bottom-up and top-down pre-listening activities on Iranian EFL students’ listening comprehension. It also investigated the potential interaction effects of language proficiency and gender with the treatments. Using the TOEFL (PBT) test, 270 learners were selected and grouped into three proficiency levels of elementary, intermediate, and upper-intermediate. At each level, 90 subjects were randomly distributed to one control (CG) and two experimental groups (EGs), each consisting of 30 learners. After giving the pretest, vocabulary preparation as a bottom-up pre-listening activity and content-related support as a top-down pre-listening activity were given to the two EGs for the treatment, but the learners in the CGs were demanded to listen to the audio tracks and go straight into the listening tasks without any pre-listening activities. The research lasted for six weeks and 12 sessions. At the end of the experiment, the posttest was given to the subjects to measure the effects of the treatments. The results revealed significant differences between the learners’ pretest and posttest performance. The analyses of the data confirmed the positive impact of both types of pre-listening activities on the listening comprehension of Iranian EFL learners based on their proficiency levels. Further analyses revealed the interaction effects between proficiency levels and treatments. However, there was no interaction effect between the learners’ gender and the treatments. The findings of the study could help practitioners in the field to assign more practical tasks to improve the listening comprehension of Iranian EFL learners.